Characterization of the movement of correspondents of the University of Medical Sciences of Santiago de Cuba. - Roberto Michael Blanco Alvarez; Sonia Haila Carbonell Labadie; Christian Cascaret Cardona; Ariadna García Savigne; Sanella Rosa Leyva Argibay (Gaceta Médica Estudiantil, 2023)
Introduction: communication is one of the fundamental axes of work of the University Student Federation. The Correspondent Movement puts into effect the organization’s communication strategy.